RELASI ANTARA VISUALISASI SPASIAL DAN ORIENTASI SPASIAL TERHADAP PEMAHAMAN KONSEP GEOMETRI RUANG - Jelatu, Silfanus; Mandur, Kanisius; Jundu, Ricardus; Kurniawan, Yohanes (STKIP Santu Paulus Ruteng, 2018)
Geometry is one of the critical subjects of mathematics. It includes concepts as points, lines, planes, space and their relations. Representations of three-dimensional objects using two-dimensional diagrams bring the difficulties of identification of their properties. The subfactors of spatial ability were identified as the primary variables in the performances of students related to geometry subject. The purpose of this study is to investigate the relationship between spatial visualisation and spatial orientation to the students understanding of space geometry concepts matter of the eighth-grade students. There are 60 eighth grade students as a  sample of the study. The reliability and the validity studies of the tests were carried out In the first part of the study. In the second part, correlation and regression analyses were carried out. Significant correlations were found between each factor. For clarifying the relationships between more than one-factor multiple regression analyses were used. The results showed that the two predictor variables explained the 65,61 % of the variance in plane geometry test scores. However, a degree of contribution of each factor differed. The relative impact of spatial orientation ability (B=. 55) was higher than the spatial visualisation ability (B=. 28).